Pharmacological Management of Diabetic Macular Edema in Real-Life Observational Studies. (28th August 2018) - Kodjikian, Laurent; Bellocq, David; Mathis, Thibaud
Abstract : Objectives of the Study. Summary of observational studies concerning the pharmacological management of diabetic macular edema (DME). Methods. A literature review was conducted using the PubMed database on 1 February 2018 to identify studies evaluating the efficacy of anti-VEGF and dexamethasone (DEX) implants for DME. Studies with more than 10 patients and follow-up of more than 6 months were selected. Analyses were carried out on the overall population and on subgroups defined according to baseline visual acuity (BVA) and the patients' naïve or non-naïve status. Results. Thirty-two studies evaluating the efficacy of anti-VEGF and 31 studies evaluating the efficacy of DEX-implants were retained, concerning 6, 842 and 1, 703 eyes, respectively. A mean gain of +4.7 letters for a mean of 5.8 injections (mean follow-up: 15.6 months) and +9.6 letters for a mean of 1.6 injections (10.3 months) was found in the anti-VEGF and DEX-implant studies, respectively. Final VA appears to be similar for both treatment (62 letters for anti-VEGF, 61.2 letters for DEX-implant), and BVA appears lower for DEX-implant, which may partially explain the greater visual gain. The DEX-implant studies show greater gains in VA compared to the anti-VEGF studies, especially for higher BVA. Indeed, mean gains for the subgroups of patients with BVA<50 letters, 50<BVA<60 letters, and BVA>60 letters are +4.3, +5.8, and +3.1 letters, respectively, in the anti-VEGF studies and +10.5, +9.3, and +8.8 letters, respectively, in the DEX-implant studies. Regarding the patient's initial status, only naïve status appears to confer the best functional response in DEX-implant studies. Conclusion. Observational studies investigating DEX-implant report clinically similar final VA when compared to anti-VEGF, but superior visual gains in real-life practice. This latter difference could be due to the better BVA, but also to the fact that less injections were administered in the anti-VEGF observational studies than in the interventional studies.